Potential benefits of biochar in agricultural crop productivity - Pérez-Cabrera, Carlos Alberto; Juarez-Lopez, Porfirio; Anzaldo-Hernández, José; Alia-Tejacal, Irán; Salcedo-Pérez, Eduardo; Balois-Morales, Rosendo (Revista Mexicana de Ciencias Agrícolas, 2021)
Biochar is a carbon-rich solid porous material obtained by the thermochemical conversion of biomass and organic materials of agricultural or forestry origin in a limited or oxygen-devoid environment. In this review paper, two objectives were set: 1) to provide an overview of biochar production techniques; and 2) conduct a review of the effect of biochar on crop growth and productivity. Studies on biochar in agriculture conducted in Mexico, production costs, as well as research trends and prospects are included. The search for scientific articles on biochar in agricultural crop productivity published in the period from January 2011 to December 2020 was carried out through the Web of Science, Dialnet, Redalyc and Scielo databases. This review shows that in the last 10 years there is an increase in research on the use of biochar in agriculture, because most research has reported positive effects on crop growth and yield, it is also necessary to increase research on biochar made with plant biomass and locally available organic materials. Most studies of biochar in agriculture have been conducted in cereals and some vegetables, so it is necessary to carry out investigations of the effect of biochar on ornamental plants, as well as on aromatic herbs and medicinal plants.
Keywords: biochar; crop yield; hydrothermal carbonization; pyrolysis; soil improver